Evaluasi Kelayakan Ekologis dan Keruangan Usulan Taman Hutan Raya di Sebagian Wilayah Kebun Raya Katingan: Evaluation of the Ecological and Spatial Feasibility of the Proposed Grand Forest Park in Part of the Katingan Botanical Gardens Area - Santosa Yulianto; Antonius Triyadi; Hendra Toni; Yosep Yosep; Herwin Joni; Reri Yulianti; Arifta Arifta (JURNAL HUTAN TROPIKA, 2026)
This study evaluates the ecological and spatial feasibility of a 12.81-hectare Convertible Production Forest area located within the Katingan Botanical Garden, Katingan Regency. The researcher aims to formulate the feasibility of this area becoming a Grand Forest Park. The researcher applied a spatial analysis method using satellite imagery and drone orthophotos. The researcher also conducted direct vegetation surveys and wildlife observations. Spatial analysis results prove that very dense canopies dominate an area of 11.60 hectares. Biophysical analysis confirms the presence of a heath forest ecosystem on the Pakau land system with high acidity and low nutrients. Biodiversity surveys identified 31 plant species from 11 families, dominated by Daha Bahandang and Terantang trees. The research team also recorded 47 fauna species and found direct evidence of critically endangered species, including Bornean Orangutan (Pongo pygmaeus) nests and Sun Bear (Helarctos malayanus) claw marks. Local communities provide strong support for the conservation plan due to ecotourism economic development potential. This study concludes that the area perfectly meets the technical criteria to change its status to a Grand Forest Park as an in-situ conservation center and urban ecological buffer.